Comparative Study on Toxicity of Synthetic Pyrethroids And Azadirachtin Insecticides in Experimental Rats - Haggag, Yasser; Habib, Heba; Ayoub, Mousa; Nossair, Mohammad; Awad, Warda; Elfeil, Wael (Zenodo, 2020)
The current work was planned to compare the toxic effects of a commercially available insecticide (Butox ® 50%) that was widely used in the Egyptian veterinary field with Achook ® insecticide (a product of agricultural application only) derived from neem ( Azadirachta indica ) seed oil extract on the experimental animals in a trail to predict their side effects if used topically upon livestock and accidently ingested or licked by animal. The insecticides toxicity was evaluated on basis of signs of toxicity, changes of biochemical parameters of experimental animals in addition to histopathological findings observed in examined internal organs. Statistical analysis clarified that the total body weight of Butox ® 50% treated groups had a significant increase than the weight of control group. On contrary, Achook 0.15% insecticide did not have any significant effect on the body weight as weight did not changed when compared with control group. Butox ® 50% and Achook 0.15% insecticides caused no significant signs of toxicity or mortalities indicating high safety margin of azadirachtin on non-target organisms. Butox ® 50% toxicity on overdose led to significant decrease of ALT, AST, ALP and LDH which may be a result of severe liver damage. Hypercholesterolemia was observed that may be due to the ability of pyrethroids to disrupt lipid metabolism in liver. Finally, there was a reverse relation between AChE and testosterone hormone was already observed in the results of the tested insecticides and it is worth mentioning that Achook insecticide caused the highest increase in AChE and the lowest level of testosterone hormone when compared with the control group and other insecticide groups. The histopathological examination of selected tissues showed that the safest insecticide was Achook 0.15% as it led to the least alterations in liver and kidney tissues; in addition, it did not produce any changes in histology of other organs as brain and testes unlike Butox ® 50% insecticide. : {"references": ["Abdel Daim, M.M., Abuzead, S.M. and Halawa, S.M., (2013): Protective role of Spirulina platensis against acute deltamethrin-induced toxicity in rats. Plos one, 8(9), p.e72991. Abdel Megeed, A. I., Radwan, U. M., Hindy, A. Z. and El Zarook, A. (2001): liver function under stress of certain common pesticides residue used in fruits and vegetables orally administrated. Ann. Agr. Sci. Cairo. 46, 343-404. Abou-Tarboush, F. M., El-Ashmaoui, H. M., Hussein, H. I., Al-Rajhy, D. and A-Assiry, M. (2009): Effect of azadirachtin of neemix-4.5 on SWR/J mice. Saudi J. of Biol. Sci., 16, 69-76. Akhtar, N., Khan, B. A., Majid, A., Khan, H. M., Mahmood, T., Gulfi shan, et al. (2011): Pharmaceutical and Biopharmaceutical evaluation of extracts from different plant parts of indigenous origin for their hypoglycaemic responses in rabbits. Acta. Pol. Pharm. 68, 919-25. Aladakatti, R. H., Sukesh, B., Jadaramkunti, U. C. and Hiremath, M. B. (2011): Aspects of the antiandrogenic/antifertility property of azadirachtin-A from Azadirachta indica leaves in male albino rats: effect on biochemical and caudal epididymal sperm parameters. Recent Research in Sci. and Technol. 3 (2), 34-46. Al-Rajhi, D., Hussein, H. I., El-Osta, M. S. and Ali, A. G. (2000): Larvicidal and ovipositional activity of Calotropis procera, neemazal/T and Eucalyptus spp against Culex pipiens. Pest. Cont. Environ. Sci. 8, 15\u201326. Amin, K. A. and Hashem, K. S. (2012): Deltamethrin-induced oxidative stress and biochemical changes in tissues and blood of catfish (Clarias gariepinus): antioxidant defense and role of alpha-tocopherol. BMC Vet. Res. 8, 45. Ashafa, A. O. T., Orekoya, L. O. and Yakubu, M. T. (2012): Toxicity profile of ethanolic extract of Azadirachta indica stem bark in male Wistar rats. Asian Pacific J. Tropic. Biomed., 811-817. Chang, B., Ge, J. H., Pei, X. S. and Liang, Y. X. (2007): Subchronic Toxicity of Biopesticide Azadirachtin (AZ). J. Indust. Heal. Occup.Dise. -BEIJING-. 33 (3): 144. Charlton M. R. (1996): Protein metabolism and liver disease. Baillieres Clin. Endocrinol. Metab. 10 (4), 617-35. Doumas, B. T., Watson, W. A. and Biggs, H. G. (1971): Albumin standards and the measurement of serum albumin with bromcresol green. Clinica. Chimica. acta, 31 (1), 87-96. El Zayat, E. L., Rawi, S. and Ismail, N. (2008): Effects of delayed acute Deltamethrin toxicity on blood and brain monoamines and free amino acids. Res. J. Environ. Toxicol. 2, 35-52. Ells, J. T., Bandettini, P. A., Holman, P. A. and Propp, J. M. (1992): Pyrethroid insecticide-induced alterations in mammalian synaptic membrane potential. Journal of Pharmacol. Exper. Therap., 262 (3), 1173-1181.\u200f El-Sayed, Y. S., Saad, T. T. and El-Bahr, S. M. (2007): Acute intoxication of deltamethrin in monosex Nile tilapia, Oreochromis niloticus with special reference to the clinical, biochemical and haematological effects. Environ. Toxicol. Pharmacol. 24, 212\u2013217. Eraslan, G., Bilgili, A., Essiz, D., Akdogan, M. and Sahindokuyucu, F. (2007): The effects of deltamethrin on some serum biochemical parameters in mice. Pesti. Bioch. physiol. 87 (2), 123-130.\u200f Fossati, P., Prencip, L. and Berti, G. (1980): Use of 3, 5-dichloro-2-hydroxybenzenesulfonic acid/4-aminophenazone chromogenic system in direct enzymic assay of uric acid in serum and urine. J. Clin. Chem. 26, 227-231. Garcia, M. V., Matias, J., Barros, J. C., Pires de Lima, D., Lopes, R. S. and Andreotti, R. (2012): Chemical identification of Tagetes minuta Linnaeus (Asteraceae) essential oil and its acaricidal effect on ticks. Rev. Bras. Parasitol. Vet. Jaboticabal. 21 (4): 405-411. Gupta, S., Kataria, M., Gupta, P. K., Vijjan, V. K. (2001): Effect of petroleum ether extracts of different parts of neem seed (Azadirachta indica) on haematological and biochemical parameters in rats. Ind. J. Anim. Res. 35, 21\u201326. Hanhong, W. Y. F. Z. X., and Li, C. (2001): Screening for Nemaicidal Activity of Some Chinese Plant Extracts against Plant Parasitic Nematodes, Bursaphelenchus xylophilus, Meloidogyne arenaria and Hirschmanniella oryzae [J]. J. Huazhong Agricul., 3. Holmes, R. W., Anderson, B. S., Phillips, B. M., Hunt, J. W., Crane, D. B., Mekebri, A. and Connor, V. (2008): Statewide investigation of the role of pyrethroid pesticides in sediments toxicity in California's urban waterways. Environ. Sci. Technol. 42, 7003\u20137009. Hyunjoo, Y., Miseon, C., Hyeon-Jo, C., Beom Seok, H., Kyung-Hun, P., Jin-Ah, O., Namjun, C. and Min-Kyoung, P. (2014): Study of Kidney Toxicity of Azadirachta Indica Extract for Oral Administration in Rats. Korean J. Environ. Agricul., 33 (2), 103-110. IFCC (International Federation of Clinical Chemistry), (2002a): Primary reference procedures for measurement of catalytic activity concentrations of enzymes at 37 C, Part 5. Reference procedure for the measurement of catalytic concentration of aspartate aminotransferase. Clin. Chem. Lab. Med. 40, 725-733. IFCC (International Federation of Clinical Chemistry), (2002b): Primary reference procedures for measurement of catalytic activity concentrations of enzymes at 37 C, Part 9. Reference procedure for the measurement of catalytic concentration of alkaline phosphatase. Clin. Chem. Lab. Med. 49, 1439-1446. IFCC (International Federation of Clinical Chemistry), (2011): Primary reference procedures for measurement of catalytic activity concentrations of enzymes at 37 C, Part 5. Reference procedure for the measurement of catalytic concentration of aspartate aminotransferase. Clin. Chem. Lab. Med. 40, 725-733. Issam, C., Intissar, G., Fatma, B., Yahia, H. M., Samir, H., Zohra, H. and Hassen, B. (2012): Oxidative Stress, Biochemical and Histopathological Alterations in the Liver and Kidney of Female Rats Exposed to Low Doses of Deltamethrin (DM): A Molecular Assessment. Biomed. Environ. Sci. 25 (6), 672-683. Jelodar, G. A., Maleki, M., Motadayen, M. H. and Sirus, S. (2005): Effect of fenugreek, onion and garlic on blood glucose and histopathology of pancreas of alloxan-induced diabetic rats. Indian J. Med. Sci. 59, 64-9. Jendrassik, L. and Grof, P. (1938): Simplified photometric methods for the determination of the blood bilirubin. Biochem. Z, 297 (81): 5. Kaplan, L. A. et al., (1984a): Kaplan L. A. Glucose. Clin Chem. The C. V. Mosby Co. St Louis. Toronto. Princeton. 1032-1036. Kaplan, L. A. et al., (1984b): Kaplan L. A. Urea. Clin Chem. The C. V. Mosby Co. St Louis. Toronto. Princeton. 1257-1260. Kaplan, L. A. et al., (1984c): Murray R. L. Creatinine. Clin Chem. The C. V. Mosby Co. St Louis. Toronto. Princeton. 1261-1266 and 418. Kaushic, C. and Upadhyay, S. (1995): Mode of long-term antifertility effect of intrauterine neem treatment (IUNT). Contraception, 51 (3), 203-207.\u200f Khan, A., Ahmad, L. and Khan, M. Z. (2012): Hemato-Biochemical Changes Induced by Pyrethroid Insecticides in Avian, Fish and Mammalian Species. Inter. J. Agricul. & Biol., 14 (5), 834\u2013842.\u200f Kumar, S., Lata, S. and Gopal, K. (1999): Deltamethrin induced physiological changes in freshwater catfish Heteropneustes fossilis. Bulletin of environ. Contam. Toxicol., 62 (3), 254-258.\u200f Kupradinun, P., Tepsuwan, A., Tanthasri, N., Meesiripan, N., Tunsakul, S., Tompat, W., Jarratwisarutporn, Y. and Kusamran, W. R. (2010): Toxicity Testing of Flowers of Neem Tree (Azadirachta indica A. Juss). Thai. J. Vet. Med. 40 (1), 47-55. Magadum S., Mondal, D. B. and Ghosh, S. (2009): Comparative efficacy of Annona squamosa and Azadirachta indica extracts against Boophilus microplus Izatnagar isolate. Parasitol. Res. 105, 1085\u20131091. Manna, S., Bhattacharyya, D., Mandal, T. K. and Das S. (2005): Repeated dose toxicity of deltamethrin in rats. Indian Pharmacol. 37, 160-164. Meiattini, F., Prencip, L., Bardelli, F., Giannini, G. and Tarli, P. (1978): The 4-hydroxybenzoate/4-aminophenazone chromogenic system used in the enzymic determination of serum cholesterol. J. Clin. Chem., 24, 2161-2165. Moid, N., Desai, K. R., Korat, V. P., Shah, I. K., Highland, H. N. and George, L. B. (2014): Hemato-biochemical effects of technical grade deltamethrin in Swiss albino male mice, Mus musculus. Int. J. Pharm. Sci. Health Care, 2 (4), 54-66. Mordue, A. J., Morgan, E. D. and Nisbet, A. J. (2010): Azadirachtin, a natural product in insect control. In: Comprehensive Molecular Insect Science. (Eds. L.I. Gilbert, K. Iatrou and S.S. Gill), Elsevier, Amsterdam, 117-134. Nawab, A., Aleem, A. and Malik, A., (2003): Determination of organochlorine pesticides in agricultural soil with special reference to \u03b3-HCH degradation by Pseudomonas strains. Biores. Technol., 88 (1): 41-46. Oda, S. S. and El-Maadawy, Z. K. (2012): Protective effect of vitamin E and selenium combination on deltamethrin-induced reproductive toxicity in male rats. Exp Toxicol Pathol., 64 (7), 813-819. Osadebe, P. O., Okide, G. B. and Akabogu, I. C. (2004): Study on anti-diabetic activities of crude methanolic extracts of Loranthus micranthus (Linn.) sourced from different host trees. J. Ethnopharmacol., 95, 133-138. Panda, S. and Kar, A. (2000): How safe is neem extract with respect to thyroid function in male mice? Pharmacol. Res. 41 (4), 419-422. Park, K., Yoon, H., Han, B. S., Lee, J., Jeong, M. H., Cho, N., Om, A. S. and Paik, M. (2014): Azadirachta indica Extract on Hepatotoxicity in Rats. Korean J Environ Agric. 33 (4), 395-402. Parveen, M., Sharma, R. and Kumar, S. (2004): Effect of Neemta 2100 toxicity on acetylcholinesterase and serum glutamate oxaloacetate transaminase enzymes in serum of fish, Oreochromis mossambicus. Indian J. Fisheries Association. 31, 97-100.\u200f Radwan, M. U., Hindy, Z. A., Abdel Megeed, M. and El Zrook, A. (2001): Residual activity of orally administrated pesticides used on fruits and vegetables on rat blood parameters behaviour. Ann. Agricul. Sci. Cairo. 46, 365\u2013382 (abstract). Rahman, M. F., Siddiqui, M. K. J. and Jamil, K. (2001): Effects of Vepacide (Azadiracht aindica) on aspartate and alanine aminotransferase profiles in a subchronic study with rats. Hum. Exp. Toxicol. 20, 243\u2013249. Raizada, R. B., Srivastava, M. K., Kaushal, R. A. and Singh, R. P. (2001): Azadirachtin, a neem biopesticide: subchronic toxicity assessment in rats. Food Chern Toxicol. 39, 477-483. Raji, Y., Udoh, U. S., Mewoyeka, O. O., Ononye, F. C. and Bolarinwa, A. F. (2003): Implication of reproductive endocrine malfunction in male antifertility efficacy of Azadirachta indica extract in rats. African J. Medicine and Medical Sci., 32 (2), 159-165.\u200f Rodkey, F. L. (1964): Binding of bromocresol green by human serum albumin. Archives of Bioch. Bioph. 108 (3), 510-513.\u200f Sami, A. J., Bilal, S., Khalid, M., Shakoori, F. R., Ur Rehman, F. and Shakoori, A. R. (2016): Effect of Crude Neem (Azadirachta indica) Powder and Azadirachtin on the Growth and Acetylcholinesterase Activity of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). Pakistan J. Zool. 48 (3), 881-886.\u200f SAS, (2004): Statistical analysis system. SAS User's Guide. SAS incorporation Institute. Shaikh, M. A., Naqvi, S. N. H. and Chaudhry, M. Z. (2009): Effect of neem oil on the structure and function of the mature male albino rat testes. Braz. J. Morphol. Sci. vol. 26 (1), 49-54. Shailey, S. W. and Basir, S. F. (2012): Protective role of Azadirachta indica against oxidative damage in skeletal and cardiac muscle of alloxan diabetic rats. Int. J. Pharm. Sci. 4, 471-7.\u200f Srivastava, M. K. and Raizada, R. B. (2007): Lack of toxic effect of technical azadirachtin during postnatal development of rats. Food and chemical toxicol., 45 (3), 465-471.\u200f Suwanchaichinda, C., Khamkong, P., Worasuttayangkum, L. and Satayavivad, J. (2005): Deltamethrin exposure affects host resistance to plasmodium infection in mice. Environmental Toxicology and Pharmacol. 20, 77-82. Tahir, S., Anwar, T. and Jabbar, A. (1992): Acetylcholinesterase activity of blister beetle exposed to synthetic and natural insecticides. Pakistan J. Agricul. Res. 13(4), 373-376.\u200f Tewari, A. and Gill, J. P. S. (2014): Assessment of hemato-biochemical parameters on exposure to low level of deltamethrin in mouse model. Vet. World. 7 (3), 152-157. Thomas, L. (1992): Ed. Labor and Diagnose 4th ed. Marburg: Die Medizinische Verlagsgesellschaft. Tietz, N. W. and Saunders, W. B. (1999): Textbook of Clinical Chemistry, Philadelphia. Toman, R., Mass\u00b4anyi, P., Adamkovicova, M., Lukac, N., Cabaj, M. and Martiniakova, M. (2012): Quantitative histologic alanalysis of the mouse testis after the long-term administration of nickel in feed. Journal of Environmental Science and Health AToxic/Hazardous Substances and Environ. Engin. 47 (9): 1272\u20131279. Unigwe, C. R., Balogun, F. A., Okorafor, U. P., Odah, I. S., Abonyi, F. O. and Olona, J. F. (2016): Effect of neem leaf (Azadirachta indica) meal on growth performance and haematology of rabbits. WSN. 55, 51-62. USEPA (U.S. Environmental Protection Agency) (1991): Methods for measuring the acute toxicity of effluents to freshwater and marine organisms. W. Pelter and C. I. Weber. eds., 4th Ed., Enveromental Monatoring and Support laboratory, Cincinnati, OH., USA. Vais, H., Williamson, M. S., Devonshire, A. L. and Usherwood, P. N. R. (2001): The molecular interactions of pyrethroid insecticides with insect and mammalian sodium channels. Pest Management Scien., 57 (10), 877-888. Vani, T., Saharan, N., Mukherjee, S. C., Ranjan, R., Kumar, R. and Brahmchari, R. K. (2011): Deltamethrin induced alteration of hematological and biochemical parameters in fingerlings of Catla catla (Ham.) and their amelioration by dietary supplement of vitamin C. pesticide Bioch. Physiol. 101, 16-20. Weichselbaum, T. E. (1946): An accurate and rapid method for the determination of proteins in small amounts of blood serum and plasma. American J. Clin. Pathol., 10, 40-49. Wheeler, M. J. (1995): The determination of bio-available testosterone. Ann. Clin. Biochem. 32, 345-357. Yan, C., Zhang, Z. X., Xu, H. H. and An, S. S. H. (2012): Library responsive to azadirachtin A constructed in Spodoptera litura Fabricius cell lines. J. Biotechnol. 159 (1-2), 115-20. Yavuz, O. Aksoy, A., Das, Y. K., Gulbahar, M. Y., Yarim, G. F., Cenesiz, M., Atmaca, E. and Guvenc, D. (2010): Repeated-dose 14-day dermal toxicity of different combinations of some synthetic pyrethroid insecticides, piperonyl butoxide, and tetramethrin in rats Cutaneous and Ocular Toxicol. 29 (1): 16\u201325. Yavuz, O., Aksoy, A., Das, Y. K., Gulbahar, M. Y., Guvenc, D., Atmaca, E., Yarim, F. G. and Cenesiz, M. (2012): Subacute oral toxicity of combinations of selected synthetic pyrethroids, piperonyl butoxide, and tetramethrin in rats. Toxicol. Indus. Heal., 31 (4): 289\u2013297. Yousef, M. I., Awad, T. I. and Mohamed, E. H. (2006): Deltamethrin-induced oxidative damage and biochemical alterations in rat and its attenuation by vitamin E. Toxicol. 227 (3): 240-247. Yousef, M. I., El-Demerdash, F. M., Kamel, K. I. and Al-Salhen, K. S. (2003): Changes in some hematological and biochemical indices of rabbits induced by isoflavones and cypermethrin. Toxicol. 189 (3), 223-234.\u200f"]}